Investigation of the individual genetic evolution of SARS-CoV-2 in a small cluster during the rapid spread of the BF.5 lineage in Tokyo, Japan - Jin, Bo; Oyama, Rieko; Tabe, Yoko; Tsuchiya, Koji; Hando, Tetsuya; Wakita, Mitsuru; Yan, Yan; Saita, Mizue; Takei, Satomi; Horiuchi, Yuki; Miida, Takashi; Naito, Toshio; et al. (Frontiers in Microbiology, 2023)
Monitoring genetic mutations is critical since SARS-CoV-2 continues to spread in some areas, posing potential healthcare risks. Mutations that occur during viral replication can be selectively retained, leading to changes in infectivity and pathogenicity. Genetic mutations that occur through cluster infections can contribute to the spread of the virus within the cluster and could potentially influence the virus' evolution in other regions. Accurately understanding the quality of genetic mutations is also crucial for the development of vaccines and treatments. However, despite the importance of the virus genome mutation process, few studies have investigated this aspect. In this research, we conducted a genomic sequence analysis of a small Omicron BA.5 lineage cluster. All members of this cluster recovered without requiring any treatment. Our findings reveal that this cluster shared some common mutations and was classified as the Omicron variant BF.5. We also identified some lowfrequency mutations. This cluster occurred during a one-week period between June and July 2021, when the Omicron sub-lineage BF.5 was spreading in Tokyo, Japan, alongside the dominant BA.5 sub-lineage. Furthermore, we have reported on the location of genetic mutations that occurred in each individual of this cluster and discussed their potential functional implications in relation to the corresponding genes.